Tracking phases of the fall armyworm (Spodoptera frugiperda) invasion across multiple continents using news media - Kathryn Bjorklund; Melissa A. Barton; Stefan Daume; Peter Søgaard Jørgensen (Biological Invasions, 2026)
Understanding cascading social-ecological impacts of emerging pests is key for addressing the challenges they introduce in an ever more interconnected and rapidly changing world. Here we examine shifts in news media discourse surrounding the fall armyworm invasion across Africa, Asia, and Oceania to investigate such cascades. We apply topic modeling to 570 news articles to quantify spatial and temporal changes in the prevalence of 33 topics related to fall armyworm invasion discourse. We grouped these topics into broader thematic categories and determined their prevalence during three general invasion phases. We found that the sequence of prevalent thematic categories was consistent across news articles from the three continents analyzed. The first years of invasion discourse are dominated by topics related to a preparation-oriented ‘Surveillance’ phase, followed by those related to an ‘Impact’ phase, and finally a response-centered ‘Control’ phase. However, the duration of the ‘Impact’ phase differs by continent, lasting 3 of the 7 years analyzed in Africa, but only 1 of 5 and 1 of 3 in Asia and Oceania, respectively. Also in Oceania’s news discourse, invasion preparation features more prominently with a relative theme proportion of 0.722 in the first year after detection (Africa = 0.387, Asia = 0.259). These differences in phase duration and emphasis align with described patterns of the invasion progression and outcomes across regions. These regional variations highlight the potential of text analysis of news media for tracking cascading dynamics of emerging pests. In turn, these approaches can inform more targeted management and mitigation strategies.